2020
DOI: 10.1093/mnras/staa3396
|View full text |Cite
|
Sign up to set email alerts
|

The large-scale magnetic field of Proxima Centauri near activity maximum

Abstract: We report the detection of a large-scale magnetic field at the surface of the slowly-rotating fully-convective M dwarf Proxima Centauri. Ten circular polarization spectra, collected from April to July 2017 with the HARPS-Pol spectropolarimeter, exhibit rotationally-modulated Zeeman signatures suggesting a stellar rotation period of 89.8 ± 4.0 d. Using Zeeman-Doppler Imaging, we invert the circular polarization spectra into a surface distribution of the large-scale magnetic field. We find that Proxima Cen hosts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 66 publications
3
45
0
Order By: Relevance
“…Prox Cen is expected to have a relatively weak stellar wind, with a mass-loss rate of 𝑀 < 0.2 𝑀 (Wood et al 2001), where 𝑀 = 2×10 −14 𝑀 yr −1 is the solar wind mass-loss rate. The star also possesses a strong large-scale surface magnetic field of ∼ 200 G (Klein et al 2021). Its proximity to Earth along with its potentially habitable planet make it an interesting system to search for planet-induced radio emission.…”
Section: Introductionmentioning
confidence: 99%
“…Prox Cen is expected to have a relatively weak stellar wind, with a mass-loss rate of 𝑀 < 0.2 𝑀 (Wood et al 2001), where 𝑀 = 2×10 −14 𝑀 yr −1 is the solar wind mass-loss rate. The star also possesses a strong large-scale surface magnetic field of ∼ 200 G (Klein et al 2021). Its proximity to Earth along with its potentially habitable planet make it an interesting system to search for planet-induced radio emission.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the results of Lafarga et al (2021), the K I line studied here appears to provide a powerful indicator of the changing photospheric magnetic field on these stars, which may be expected to perform well as a tracer of rotational modulation, and as an RV activity indicator. Recently, Klein et al (2021) used Zeeman Doppler Imaging to recover the magnetic field geometry of Proxima Centauri, an old, slowly-rotating, fully-convective star similar to GJ 699 and Teegarden's Star (albeit more active). They additionally found a significant rotational modulation in Stokes I spectra of Proxima Cen, and discuss the value of contrasting polarized and unpolarized indicators for diagnosing the properties of the dynamos of these fully-convective stars.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have been leveraged to estimate the total magnetic fields of several M dwarfs (Shulyak et al 2019;Moutou et al 2017), and have also revealed apparent saturation behavior of the dynamo (Reiners et al 2009;Muirhead et al 2020). Measurements of unpolarized Zeeman signatures have even revealed rotational modulation in a small number of cases (Kochukhov & Lavail 2017;Klein et al 2021), and may contribute to the periodic variability observed in numerous lines in M dwarf spectra (Lafarga et al 2021).…”
mentioning
confidence: 99%
“…The M dwarfs in our sample with spectropolarimetric constraints are EV Lac (Morin et al 2008b), YZ CMi (Morin et al 2008b), Proxima Cen (Klein et al 2021), andGJ 205 (Hébrard et al 2016). There are nine other stars in Table 3 with spectropolarimetric measurements.…”
Section: Relating ṁ and Magnetic Topologymentioning
confidence: 99%